CREATIVE TECHNIQUES AND PEDAGOGICAL MASTERY IN TECHNICAL EDUCATION - Salijonova Shakhnozakhon Dilmurodovna (Bright Mind Publishing, 2025)
This article explores the importance of pedagogical technique in technical education and its role in enhancing teaching effectiveness. Pedagogical technique represents a combination of practical skills that enable teachers to communicate efficiently, inspire students’ interest, and facilitate both theoretical and practical learning. In the technical field, teaching goes beyond delivering theoretical knowledge it requires developing students’ practical competencies, such as operating machines or devices. The study highlights two main groups of pedagogical techniques: (1) teacher’s self-regulation skills, which include managing behavior, emotions, speech, and gestures to build trust and professional influence; and (2) communication skills with students, focusing on clear verbal explanations, effective questioning, and teamwork facilitation. The article concludes that mastering pedagogical technique allows teachers to make technical lessons engaging, understandable, and practice-oriented, thus preparing students for real-world professional tasks.
Keywords: pedagogical technique, technical education, communication skills, teaching mastery, practical learning, emotional control, teamwork.